Computational biomechanics in cross-country skiing - Holmberg, J. L. (Linköping Studies in Science and Technology, Thesis No. 1346, 2008)
Traditionally, research on cross-country skiing biomechanics is based mainly on experimental testing alone. Trying a different approach, this thesis explores the possibilities of using computational musculoskeletal biomechanics for cross-country skiing. As far as the author knows, this has not been done before.Cross-country skiing is both fast and powerful, and the whole body is used to generate movement. Consequently, the computational method used needs to be able to handle a full-body model with lots of muscles. This thesis presents several simulation models created in the AnyBody Modeling System, which is based on inverse dynamics and static optimization. This method allows for measurementdriven full-body models with hundreds of muscles and rigid body segments of all major body parts.A major result shown in the thesis is that with a good simulation model it is possible to predict muscle activation. Even though there is no claim of full validity of the simulation models, this result opens up a wide range of possibilities for computational musculoskeletal biomechanics in cross-country skiing. Two example of new possibilities are shown in the thesis, finding antagonistic muscle pairs and muscle load distribution differences in different skiing styles. Being able to perform optimization studies and asking and answering "what if"-questions really gives computational methods an edge compared to traditional testing.To conclude, a combination of computational and experimental methods seems to be the next logical step to increase the understanding of the biomechanics of crosscountry skiing.